Distribution of Arsenic Forms in Decomposed Solidwaste - Rukh1, Shah; Saleem Akhtar1, Mohammad; Memon2, Mehruinsa; Mehmood1, Ayaz; Imran1, Muhammad (Asian Journal of Chemistry, 2014)
Arsenic forms distribution helps to understand its chemical processes and bioavailability. Total and distribution of arsenic fractions in decomposed solidwastes measured by an atomic absorption spectrophotometer with flame heated quartz adsorption cell coupled to a hydride generation device, are reported. The system had detection limit 2.42 μg L-1 for total arsenic. The decomposed solidwaste was collected from historic dumpsites of three cities and analyzed for total by digestion in three acids and for the arsenic forms using sequential Wenzel et al. extraction scheme. Lower than reported for contaminated soil and solidwaste, total arsenic in the solid waste ranged 2.5 to 7 mg kg-1 which occurred dominantly as specifically-sorbed fraction (675 to 3070 μg kg-1) positively correlated with extractable iron oxides and dissolved organic carbon. Overall the arsenic forms followed the order amorphous and poorly-crystalline metal oxides sorbed arsenic > residual phases > well crystalline metal oxides sorbed arsenic > non-specifically sorbed arsenic fraction. This study concludes that arsenic primarily occurred as specifically sorbed fraction to iron oxides and correlation with dithionite extractable iron implied that a reducing condition (eg., prolonged submergence) may release arsenic to the environment.